Penggunaan asap cair sebagai pengawet alami bakso ikan tuna sirip kuning (Thunnus albacares) - Fahmi Hadi Alamsyah; Irfan Irfan; Dewi Yunita (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
The purpose of this study was to determine the effect of using various types of liquid smoke on the level of preference of panelists and the total of contaminant bacteria on yellowfin tuna meatballs. The liquid smoke used came from coconut shells, corncob, and bagasse. The tuna meatballs without the use of liquid smoke were also observed as a control. The tuna meatballs were analyzed before storage, after 15 days, and after 30 days storage (temperature 5oC). The research was designed by a completely randomized design (CRD) factorial pattern. The tuna meatballs were examined for organoleptic (hedonic) tests on color, flavor, taste, and texture as well as microbial tests of Staphylococcus aureus and Salmonella sp. Proximate tests (moisture content, ash content, and protein content) were carried out on meatballs with the lowest microbial total after 30 days of storage. The data obtained were analyzed using variance analysis (ANOVA). Duncan's continued Multiple Range Test (DMRT) was carried out if the treatment was significant. The results showed that adding liquid smoke to the boiling water of the meatballs can only increase the panelist's preference for color attributes. Tuna meatballs without the use of liquid smoke could not be consumed after 15 days of storage. The tuna meatballs with the addition of liquid smoke from bagasse in the boiling water have met the national standards for fish meatballs listed in SNI 7266: 2014 until 30 days of storage. The resulting yellowfin tuna meatballs had 59.76% moisture content, 1.41% ash content, and 11.8% protein content.